Sociodemographic and Nursing Characteristics of Residents With Schizophrenia in an Indonesian Social Care Home: A Descriptive Cross-Sectional Study - Intan Fidyatul Fuaidah; Mundakir Mundakir; Reliani Reliani; Nugroho Ari Wibowo; Supriyono Supriyono (Universitas Muhammadiyah Surabaya, 2026)
Background: Schizophrenia is a disabling psychotic disorder that affects perception, cognition, behavior, social participation, education, and employment. Residents of social care facilities may have additional vulnerabilities related to homelessness, disrupted family relationships, poverty, and limited continuity of care. Local descriptions of their sociodemographic and nursing characteristics can support service planning. Objective: To describe the sociodemographic characteristics and primary nursing problems of residents recorded as having schizophrenia in a social care home in Surabaya, Indonesia. Methods: A descriptive cross-sectional study used total enumeration of 80 residents with a recorded diagnosis of schizophrenia in wards A, B, C, and E of the Keputih Social Care Home. Age, sex, and educational attainment were obtained from medical records; pre-admission monthly income and marital status were collected through structured interviews; and the primary nursing problem was identified through interview and observation using a mental health nursing assessment form. Data were summarized as frequencies and percentages. Results: The largest age group was 39–46 years (23/80, 28.7%). Most residents were women (54/80, 67.5%), had completed senior secondary school (26/80, 32.5%), reported a pre-admission monthly income of IDR 0–285,000 (30/80, 37.5%), and had never married (52/80, 65.0%). Hallucinations were the most frequently recorded primary nursing problem (62/80, 77.5%), followed by risk for violent behavior (8/80, 10.0%), disturbed self-concept (5/80, 6.3%), delusions (3/80, 3.8%), and social isolation (2/80, 2.5%). Conclusion: The residents were predominantly middle-aged, female, economically disadvantaged, and never married, while hallucinations dominated the recorded nursing profile. The findings support routine multidimensional assessment, individualized symptom management, psychosocial rehabilitation, supported social participation, and coordinated plans for community reintegration. Because the study was descriptive and facility-based, the distributions should not be interpreted as risk estimates or as representative of all people with schizophrenia in Indonesia.